2021
DOI: 10.1186/s12891-021-04274-w
|View full text |Cite
|
Sign up to set email alerts
|

Femur originated genu varum in a patient with symptomatic ACL deficiency: a case report and review of literature

Abstract: Background Anterior cruciate ligament (ACL) injury may be associated with genu varum. There are a few indications in which the varus deformity can be corrected at the time of ACL reconstruction. However, as the genu varum originates mostly from the tibia and the simultaneous presence of ACL deficiency and femur originated genu varum is uncommon, only a few papers have described their management for ACL deficient patients with femur originated genu varum. Case pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, there are relevant literature reports that in addition to congenital genetic malformations [2], Acquired factors such as vitamin D deficiency [3], weight [4,5], sport events [6] are relevant to GV. Some studies have shown that GV affects people's posture and movement mode, causes the force imbalance between the inner and outer space of the knee joint, which may eventually lead to knee osteoarthritis (KOA) [7] or Anterior cruciate ligament injury [8]; GV not only affects the knee itself but also has a complex impact on the biomechanics of the lower limbs. Jeong Bo et al found that patients with GV are often accompanied by foot compensatory changes such as subtalar joint rotation and arch collapse, which leads to the change of biological force line of lower limbs and finally systemic symptoms [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are relevant literature reports that in addition to congenital genetic malformations [2], Acquired factors such as vitamin D deficiency [3], weight [4,5], sport events [6] are relevant to GV. Some studies have shown that GV affects people's posture and movement mode, causes the force imbalance between the inner and outer space of the knee joint, which may eventually lead to knee osteoarthritis (KOA) [7] or Anterior cruciate ligament injury [8]; GV not only affects the knee itself but also has a complex impact on the biomechanics of the lower limbs. Jeong Bo et al found that patients with GV are often accompanied by foot compensatory changes such as subtalar joint rotation and arch collapse, which leads to the change of biological force line of lower limbs and finally systemic symptoms [9].…”
Section: Introductionmentioning
confidence: 99%